Guided tissue regeneration in conjunction with hydroxyapatite-collagen grafts for intrabony defects - A clinical and radiological evaluation - (:unkn) unknown (WILEY, 1997)
This clinical and radiological study evaluated the healing of 3+2+1 wall-combined intrabony defects treated using the guided tissue regeneration technique (GTR) with and without hydroxyapatite-collagen alloplastic graft materials (HAC), in comparison to that of HAC alone and conventional flap surgery (CF). 40 interproximal defects with probing depth >6 mm were treated in 18 adult periodontitis patients of ages 35-60 years. After non-surgical therapy, the defects were randomly grouped into 4 groups of 10 defects each. These groups were designated: (1) expanded polytetrafluoroethylene membrane (e-PTFE), (2) e-PTFE+HAC, (3) HAC alone and (4) CF. At 6 months, the following changes in parameters were recorded. Mean PPD reduction for each group was 5.83, 5.85, 3.80 and 3.17 mm respectively. PPD reduced very significantly in all groups (p<0.01), the highest and lowest reductions in PPD being for the e-PTFE+ HAC and CF group respectively. Comparison between the 4 groups showed higher PPD reduction in both membrane groups than in either of the non membrane groups (p<0.05) with the difference between the e-PTFE and CF groups being very highly significant (p<0.001). Mean attachment gain for the 4 groups was 3.70, 3.80, 2.60 and 2.1 mm, respectively. Similarly attachment gain for all groups was very significant (p<0.01) and the highest and lowest attachment gains were for the e-PTFE+HAC and CF group respectively. Both membrane groups showed significantly more attachment gain than the CF group (p<0.05). Change in probing bone level (BL) for the 4 groups was 1.60, 1.90, 1.0 and 0.65 mm respectively. Again the highest changes in BL were recorded for the e-PTFE+HAC group. Significant differences were found between both membrane groups and the CF group (p<0.05). Radiological evaluation using standardized radiographs and millimeter grids showed change in radiographic bone level at the deepest point of the defect on the radiograph to be 1.50, 1.55, 0.85 and 0.60 mm, respectively and this was significantly higher in both membrane groups than in the CF group (p<0.05). This study therefore found e-PTFE membranes both alone and when combined with HAC to lead tb more attachment gain and bone fill than did HAC alone or CF. It found HAC combined with e-PTFE to perform better although not significantly better than e-PTFE alone.
Keywords: guided tissue regeneration (GTR); membrane; hydroxyapatite-collagen; graft materials; intrabony defects; PERIODONTAL OSSEOUS DEFECTS; HUMAN INFRABONY DEFECTS; FREEZE-DRIED BONE; POROUS HYDROXYLAPATITE IMPLANTS; DIGITAL SUBTRACTION RADIOGRAPHY; BARRIER MEMBRANES; EPTFE MEMBRANES; CITRIC-ACID; HEALING RESPONSES; FURCATION DEFECTS